Methotrexate hydrate crystal form DCI and preparation method and application thereof

By changing the preparation method of methotrexate hydrophobic compounds, the new crystal DCI with characteristic peaks and high stability is obtained, and the problem of moisture absorption and weight gain in high humidity conditions is solved. Quality stability during transportation, storage and packaging.

CN119350340APending Publication Date: 2025-01-24BIRDO (SHANGHAI) PHARMATECH CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410872249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing methotrexate hydrates are prone to moisture absorption and gain weight under high humidity conditions, resulting in adverse effects of drugs during transportation, storage and packaging.

Method used

By changing the preparation method of methotrexate aquarmers, a new crystal DCI is obtained. The X-ray powder diffraction spectrum under CU-KA radiation has a characteristic peak, and at 105 ± 5 ℃ and 181 ± 5 ℃ There is a hot peak at the place, and the range of the aquarmers is 2.5-3, which has good solubility and stability.

Benefits of technology

This new crystal DCI has excellent slurry stability, solid stability, and mechanical stability, reducing the risk of crystal, and almost no wetness, ensuring the quality stability of the drug during storage and transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350340A_ABST
    Figure CN119350340A_ABST
Patent Text Reader

Abstract

The invention discloses methotrexate hydrate crystal form DCI (Downlink Control Information) and a preparation method and application thereof. The crystal form DCI has characteristic peaks in an X-ray powder diffraction spectrum under Cu-Ka radiation when the diffraction angle 2theta value is 8.3 + / -0.2 degrees, 10.7 + / -0.2 degrees, 12.4 + / -0.2 degrees, 13.3 + / -0.2 degrees, 14.1 + / -0.2 degrees, 14.9 + / -0.2 degrees, 15.9 + / -0.2 degrees, 16.2 + / -0.2 degrees, 16.6 + / -0.2 degrees, 17.9 + / -0.2 degrees, 20.8 + / -0.2 degrees, 21.9 + / -0.2 degrees, 24.3 + / -0.2 degrees, 24.9 + / -0.2 degrees, 25.2 + / -0.2 degrees, 26.0 + / -0.2 degrees, 27.1 + The methotrexate hydrate crystal form DCI prepared by the invention has excellent slurry stability and solid stability, reduces the risk of crystal transformation, provides more loose conditions for storage, transportation, packaging and subsequent processing and use, ensures the stability of drug quality, and plays an important role in the development of the drug.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of drug crystal forms, and in particular to a methotrexate hydrate crystal form DCI and a preparation method and use thereof. Background Art

[0002] As an antifolate drug, methotrexate has good therapeutic effects on diseases such as tumors and rheumatoid arthritis. At present, literature and patents only report on the synthesis and purification process of methotrexate, its pharmaceutical preparation form, and treatment methods. However, there is little research on the polymorphic form of methotrexate.

[0003] All drugs have polymorphism, which refers to the phenomenon that solid drug molecules have two or more different crystal forms. Different crystal forms lead to different physical and chemical properties. Different crystal forms of solid drug molecules will face different challenges during storage, such as physical changes such as crystal transformation and deliquescence during transportation and storage, which will affect the purity and content of the drug to a certain extent. Especially for hydrates, the stability of the crystal form is more important. Therefore, drug crystal form is an important part of the research and development process of solid drugs, and is also an important part of drug quality control.

[0004] The authors of the present invention discovered that methotrexate available on the market is a hydrate. When detecting the moisture content, it was found that when the ambient humidity is higher than 70% RH, the moisture content will continue to increase with the extension of the sampling detection time. It is believed that this is caused by the continuous moisture absorption and weight gain of its solid form under high humidity conditions. This phenomenon has a great adverse effect on the transportation, storage, packaging and subsequent processing of solid drugs.

[0005] The present application aims to study a methotrexate crystal form with good stability and low hygroscopicity to solve the problems existing in the prior art. Summary of the invention

[0006] In view of the above-mentioned defects of the prior art, the present invention provides a methotrexate hydrate crystal form DCI and a preparation method thereof, wherein the crystal form DCI has good solubility and stability.

[0007] In a first aspect of the present invention, a methotrexate hydrate crystalline form DCI is provided, wherein the X-ray powder diffraction spectrum of the crystalline form DCI under Cu-Ka radiation is 8.3±0.2°, 10.7±0.2°, 12.4±0.2°, 13.3±0.2°, 14.1±0.2°, 14.9±0.2°, 15.9±0.2°, 16.2±0 .2°, 16.6±0.2°, 17.9±0.2°, 20.8±0.2°, 21.9±0.2°, 24.3±0.2°, 24.9±0.2°, 25.2±0.2°, 26.0±0.2°, 27.6±0.2°, 28.0±0.2°, 28.4±0.2°, 30.1±0.2°, and 31.9±0.2° all have characteristic peaks.

[0008] Furthermore, the differential scanning calorimetry spectrum of the crystalline form DCI shows endothermic peaks at 105±5°C and 181±5°C.

[0009] Furthermore, the thermogravimetric analysis spectrum of the crystalline form DCI shows that the weight loss at 25-150°C is 10%~11%.

[0010] Furthermore, the hydrate range is 2.5-3.

[0011] In a second aspect of the present invention, a method for preparing the above-mentioned methotrexate hydrate crystalline form DCI is provided, wherein methotrexate disodium salt is placed in water, and after adding an aqueous sulfuric acid solution, a solid is precipitated to obtain a suspension, and the obtained suspension is stirred, separated, and dried to obtain the crystalline form DCI.

[0012] Furthermore, the crystallization temperature is 0-50°C.

[0013] The third aspect of the present invention provides a pharmaceutical composition, characterized in that the pharmaceutical composition comprises an effective therapeutic amount of methotrexate hydrate crystalline form DCI and a pharmaceutically acceptable carrier or excipient thereof.

[0014] The fourth aspect of the present invention provides a use of a methotrexate hydrate crystalline form DCI in the preparation of a drug.

[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) The methotrexate hydrate crystal form DCI of the present invention has excellent slurry stability, solid-state stability and mechanical stability, and reduces the risk of crystal transformation. (2) The methotrexate hydrate crystal form DCI of the present invention has almost no hygroscopicity. The extremely low hygroscopicity can ensure that the sample can maintain extremely low moisture gain and no deliquescence during the later production, processing, storage and transportation, thereby ensuring the stability of the drug quality.

[0016] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the XRPD spectrum of the methotrexate hydrate crystalline form DCI prepared in Example 1 of the present invention; Figure 2 is the DSC spectrum of the methotrexate hydrate crystalline form DCI prepared in Example 1 of the present invention; Figure 3 is the TGA spectrum of the methotrexate hydrate crystalline form DCI prepared in Example 1 of the present invention; Figure 4 is the XRPD spectrum of methotrexate crystal form 1 obtained in Comparative Example 2 of the present invention; Figure 5 is the DSC spectrum of methotrexate crystal form 1 obtained in Comparative Example 2 of the present invention; Figure 6 is the TGA spectrum of methotrexate crystal form 1 obtained in Comparative Example 2 of the present invention; Figure 7 It is the XRPD superposition diagram obtained in Comparative Example 3 of the present invention; Figure 8 is an XRPD overlay of the methotrexate hydrate crystalline form DCI obtained in Comparative Example 4 of the present invention; Fig. 9 is an XRPD overlay of the methotrexate crystal form 1 obtained in Comparative Example 4 of the present invention; DETAILED DESCRIPTION

[0019] In order to make the technical means, creative features, objectives and effects of the invention easier to understand, the invention is further described below with reference to specific diagrams. However, the invention is not limited to the following implementation cases.

[0020] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings in this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0021] The present application starts from the perspective of changing the preparation method of methotrexate hydrate to obtain a new crystal form DCI of methotrexate hydrate. The crystal form DCI has higher stability under high humidity conditions and can more easily cope with extreme storage conditions. At the same time, in water, the in vivo environment can avoid the risk of crystal transformation, thereby ensuring the medication effect more stably.

[0022] XRPD, namely X-ray powder diffraction, the X-ray powder diffraction pattern of the present application was collected on a Bruker D2 PHASER X-ray powder diffractometer. The method parameters of X-ray powder diffraction are as follows: X-ray source: Cu Ka; Ka1 (A): 1.54060; Ka2 (A) 1.54439; Ka2 / Ka1 intensity ratio: 0.50; voltage: 30 kilovolts (kV); current: 10 milliamperes (mA); scanning range: 3.0-40.0°.

[0023] DSC, namely differential scanning calorimetry, the differential scanning calorimetry (DSC) graph of the present application was collected on TA company DSC X3, and the method parameters of differential scanning calorimetry (DSC) are as follows: scanning rate: 10 °C / min; protective gas: nitrogen.

[0024] TGA, namely thermogravimetric analysis, the thermogravimetric analysis (TGA) graph of the present application was collected on TA TGA55, and the method parameters of thermogravimetric analysis (TGA) were as follows: scanning rate: 10 °C / min; protective gas: nitrogen.

[0025] Unless otherwise specified, the following examples are all operated at room temperature. The "room temperature" is not a specific temperature value, but refers to a temperature range of 10-30°C.

[0026] The "stirring" described in the following examples is accomplished by conventional methods in the art, such as magnetic stirring or mechanical stirring, with a stirring speed of 50-1800 rpm, wherein the magnetic stirring is preferably 300-900 rpm, and the mechanical stirring is preferably 100-300 rpm.

[0027] The "separation" described in the following examples is accomplished by conventional methods in the art, such as centrifugation or filtration, and the "centrifugation" operation is: placing the sample to be separated in a centrifuge tube and centrifuging it at a rate of 10,000 rpm until all the solids sink to the bottom of the centrifuge tube.

[0028] The "drying" described in the following examples can be carried out at room temperature or higher. The drying temperature is from room temperature to about 50°C, or to 40°C. The drying time can be 2 to 48 hours, or overnight. The drying is carried out in a fume hood, a forced air oven, or a vacuum oven.

[0029] The "crystal" described in the following examples refers to a solid confirmed by the characterization of an X-ray powder diffraction pattern. It will be appreciated by those skilled in the art that the physicochemical properties discussed herein can be characterized, and the experimental error therein depends on the conditions of the instrument, the preparation of the sample and the purity of the sample. In particular, it is well known to those skilled in the art that the X-ray powder diffraction pattern will usually change with the different instrument conditions. It is particularly important to point out that the relative intensity of the diffraction peaks in the X-ray powder diffraction pattern may also change with the change of the experimental conditions, so the order of the diffraction peak intensity cannot be used as the only or decisive factor. In fact, the relative intensity of the diffraction peaks in the X-ray powder diffraction pattern is related to the preferred orientation of the crystal, and the diffraction peak intensity shown in the present invention is illustrative rather than for absolute comparison. In addition, the experimental error of the diffraction peak position is usually 5% or less, and the errors of these positions should also be taken into account, and an error of ±0.2 is usually allowed. In addition, due to the influence of experimental factors such as sample thickness, the overall offset of the diffraction peak angle will be caused, and a certain offset is usually allowed. Therefore, it can be understood by those skilled in the art that the X-ray powder diffraction pattern of the protected crystal form of the present invention is not necessarily completely consistent with the X-ray powder diffraction patterns in the embodiments referred to herein, and any crystal form having an X-ray powder diffraction pattern that is the same as or similar to the characteristic peaks in these patterns falls within the scope of the present invention.

[0030] A person skilled in the art can compare the X-ray powder diffraction patterns listed in the present invention with the X-ray powder diffraction patterns of an unknown crystal form to confirm whether the two sets of patterns reflect the same or different crystal forms.

[0031] The crystal form DCI of the present invention is pure and substantially free of any other crystal forms. In the present invention, "substantially free" when used to refer to a new crystal form means that the crystal form contains less than 20% (by weight) of other crystal forms, particularly less than 10% (by weight) of other crystal forms, more particularly less than 5% (by weight) of other crystal forms, and even more particularly less than 1% (by weight) of other crystal forms.

[0032] The term "about" in the present invention, when used to refer to a measurable value, such as mass, time, temperature, etc., means that there is a certain floating range around the specific value, which can be ±10%, ±5%, ±1%, ±0.5% or ±0.1%.

[0033] Methotrexate hydrate as a raw material includes but is not limited to solid form (crystalline or amorphous), oily, liquid form and solution. Preferably, it is in solid form.

[0034] In the process of preparing the methotrexate hydrate crystal form DCI in the present application, there is no strict restriction on the amount of methotrexate disodium salt and water used. Water is used to dissolve methotrexate disodium salt, and its amount is limited to the complete dissolution of methotrexate hydrate; and the use of aqueous sulfuric acid solution is to precipitate methotrexate hydrate. Different amounts of sulfuric acid may lead to differences in the precipitated crystal forms.

[0035] Temperature also plays a key role in the precipitation of methotrexate hydrates. Different crystallization temperatures may lead to the precipitation of different methotrexate hydrates rather than the hydrate crystal form DCI of the present application.

[0036] Different crystallization times also affect the degree of crystallization or the output of crystals, and can be flexibly selected according to actual needs.

[0037] The methotrexate hydrate crystal form DCI obtained in the present application can be in the form of tablets or capsules when administered. For the preparation of tablets or capsules, conventional excipients can be added and prepared in a conventional manner. For example, when preparing tablets, the methotrexate hydrate crystal form DCI obtained in the present application is mixed evenly with the excipients, rolled into thin slices and crushed into particles, mixed evenly with the added excipients, and pressed into shape using a suitable mold. When preparing capsules, the methotrexate hydrate crystal form DCI obtained in the present application is mixed evenly with the excipients, rolled into thin slices and crushed into particles, mixed evenly with the added excipients, and canned into capsules of suitable size.

[0038] Example 1, Preparation method of methotrexate hydrate crystal form DCI:

[0039] Weigh 5.0 g of methotrexate disodium salt and add it to a 250 ml reactor; add 75 g of purified water, heat to 35±5°C, and stir until dissolved; prepare a 1% (weight ratio) sulfuric acid aqueous solution, measure 1.83 g of 98% concentrated sulfuric acid, slowly add it to 99 g of purified water, and cool it to obtain a 1% (weight ratio) sulfuric acid aqueous solution; keep the reactor warm and stirred at 35±5°C, and slowly add 14 g of 1% (weight ratio) sulfuric acid aqueous solution thereto; keep the reactor warm and stirred at 35±5°C for more than 1 hour, at which time it is an orange-yellow slurry, and the solid is detected by XRPD as the crystalline form DCI of the present application; continue to drop 45 g of 1% (weight ratio) sulfuric acid The acid aqueous solution was added dropwise for about 30 minutes; the reactor was kept warm and stirred at 35±2°C for 1 hour; the reactor was slowly cooled to 20°C in about 1.5 hours; the reactor was kept warm and stirred at 20±5°C for 2 hours; the reactor was filtered under reduced pressure, and the filter cake was rinsed with 20 grams of purified water; the filter cake was vacuum dried at 30±5°C for 6 hours, turning the material once per hour; the vacuum oven was heated to 55±5°C and continued to dry for 18 hours; finally, 4 grams of yellow crystalline powder was obtained, which was the crystalline form DCI of the present application as determined by XRPD, with a yield of 87.5% (weight ratio).

[0040] The XRPD diagram of the crystal form DCI of the present application is as follows Figure 1 The XRPD data are shown in Table 1, and the DSC diagram is shown in Figure 2 As shown in the TGA diagram Figure 3 shown.

[0041] Table 1 Diffraction angle 2θ d value Relative Strength Diffraction angle 2θ d value Relative Strength 8.253 10.70 75.60% 21.894 4.06 7.80% 10.669 8.29 26.40% 24.3 3.66 18.10% 12.36 7.16 4.10% 24.922 3.57 8.10% 13.269 6.67 5.20% 25.247 3.52 10.40% 14.145 6.26 27.00% 25.971 3.43 23.70% 14.897 5.94 5.00% 27.613 3.23 8.80% 15.881 5.58 7.50% 27.98 3.19 16.90% 16.236 5.45 7.60% 28.424 3.14 4.80% 16.596 5.34 63.60% 30.094 2.97 10.10% 17.938 4.94 100.00% 31.912 2.80 9.70% 20.76 4.28 22.30%

[0042] from Figure 2 It can be seen that the methotrexate hydrate crystal form DCI prepared in Example 1 has two endothermic peaks at around 105°C and 181°C, respectively. Figure 3 It can be seen that the methotrexate hydrate crystal form DCI loses 10.16wt% at 25-105℃. Figure 2 and Figure 3 It can be seen that the endothermic peak near 105°C is caused by the dehydration of hydrate.

[0043] Comparative Example 1, Characterization of commercially available crystal forms of methotrexate:

[0044] Purchased from China Food and Drug Authentication Institute, national drug standard substance, batch number 100138-202207, named as reference substance crystal form 1, hereinafter referred to as crystal form 1, its XRPD pattern is as follows Figure 4 As shown, its DSC diagram is as follows Figure 5 As shown in the TGA diagram Figure 6 As shown. Figure 5 It can be seen that methotrexate crystal form 1 has an endothermic peak near 105°C. Figure 6 It can be seen that methotrexate crystal form 1 loses 6.9wt% weight at 25-105°C, and it is believed that the number of water molecules bound to it is 2. Figure 5 and Figure 6 It can be seen that the endothermic peak near 105°C is caused by the dehydration of hydrate.

[0045] Comparative Example 2, competitive slurry:

[0046] In order to compare the slurry stability relationship between the crystal form DCI of the present application and the crystal form 1 in comparative example 1, and to further understand the risk of crystal transformation that may occur in the preparation of raw materials and formulation processes of the crystal form, a suspension stirring experiment of the crystal form DCI and the reference crystal form 1 in water was specially carried out.

[0047] Weigh about 100 mg of each of the crystal form DCI prepared in Example 1 and the crystal form 1 in the comparative example, add them to a glass vial, add 4 ml of water, stir at 20±5°C, take samples at 0 hour, 2 hours, and 6 hours, centrifuge, collect solids for XRPD testing, and the XRPD overlay is as follows: Figure 7 shown.

[0048] from Figure 7 It can be seen that after stirring in water for 6 hours, the crystal form 1 completely disappears and turns into the crystal form DCI of the present application, and it is further known that the crystal form DCI of the present application is a thermodynamically stable crystal form in pure water. Therefore, the crystal form DCI of the present invention has excellent stability in water.

[0049] During the preparation, storage and formulation production (such as wet granulation), APIs cannot avoid contact with water, so the stability of samples in water is an important parameter to be investigated. The crystal form DCI of the present invention has good stability in water, which will bring convenience to sample production, storage and formulation processes, reduce the risk of crystal transformation, and improve product stability.

[0050] Table 2, Crystal stability experiment: 0 hours 2 hours 6 hours Crystal form DCI + crystal form 1 Crystal form DCI + crystal form 1 Crystalline DCI

[0051] Comparative Example 3, Hygroscopicity:

[0052] In order to understand the risk of moisture absorption and weight gain that may occur during the preparation of raw materials, formulation process, and storage of drugs, which may lead to changes in the content of raw materials and drugs, resulting in reduced efficacy and chain reactions, a hygroscopic experiment of crystal form DCI and reference crystal form 1 under high humidity conditions was conducted.

[0053] About 300 mg of the crystal form DCI prepared in Example 1 of the present application and the crystal form 1 of the comparative example were weighed respectively, placed at 25 ± 1 ° C and 92.5% relative humidity for 24 hours, and the mass of the samples before and after was recorded. The specific results are shown in Table 3 below.

[0054] Table 3 Starting mass (mg) Placement conditions Placement time Mass after placement (mg) Weight gain (mg) Weight gain percentage average value DCI 299 25 ± 1 ℃, 92.5% relative humidity 24 hours 300 1 0.3% 0.3% DCI 299 25 ± 1 ℃, 92.5% relative humidity 24 hours 300 1 0.3% 0.3% DCI 300 25 ± 1 ℃, 92.5% relative humidity 24 hours 301 1 0.3% 0.3% Crystal form 1 301 25 ± 1 ℃, 92.5% relative humidity 24 hours 311.5 10.5 3.5% 3.6% Crystal form 1 301 25 ± 1 ℃, 92.5% relative humidity 24 hours 311.8 10.8 3.6% 3.6% Crystal form 1 300 25 ± 1 ℃, 92.5% relative humidity 24 hours 310.8 10.8 3.6% 3.6%

[0055] As can be seen from Table 3, the crystalline form DCI of the present invention has significant hygroscopicity under high humidity conditions compared to the crystalline form of the reference product, while the crystalline form 1 of the comparative example has significant hygroscopicity under the same conditions, which indicates that the crystalline form DCI is not prone to hygroscopicity during drug production and storage.

[0056] Comparative Example 4, solid state stability:

[0057] In order to compare the factors and their changes that affect the solid-state stability of Form DCI and Form 1, and to provide a basis for the screening of formulation processes, the selection of packaging materials and containers, and the determination of storage conditions.

[0058] About 5 mg of the crystal form DCI prepared in Example 1 and the crystal form 1 of the comparative example were weighed, respectively, and placed open at high temperature (40°C and 60°C) and high humidity (25°C / 92.5% relative humidity) conditions, and the crystal form was determined by XRPD. The experimental conditions and results are shown in Table 2. The XRPD overlay of the crystal form DCI is shown in Figure 8 As shown, the XRPD overlay of the reference substance Form 1 is as follows Fig. 9 shown.

[0059] Table 4 Placement conditions Placement time Crystal form Crystal form Starting -- Crystalline DCI Crystal form 1 40 ℃ 5 days Crystalline DCI Crystal form 1 40 ℃ 10 days Crystalline DCI Crystal form 1 60 ℃ 5 days Crystalline DCI Crystal form 1 60 ℃ 10 days Crystalline DCI Crystal form 1 25℃ / 92.5%RH 5 days Crystalline DCI Crystal form 1 25℃ / 92.5%RH 10 days Crystalline DCI Form 1 + Form DCI

[0060] According to Table 4 and Figure 8 It can be seen that the crystal form DCI of the present invention can maintain physical stability under high temperature and high humidity conditions, providing ample conditions for processing environment, packaging, storage, etc. According to Table 4 and Fig. 9 It can be seen that Form 1 will transform into Form DCI of the present invention under high humidity conditions, which also shows that Form DCI of the present invention is more stable than Form 1.

[0061] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A methotrexate hydrate crystal form DCI, characterized in that: The X-ray powder diffraction spectrum of the crystalline form DCI under Cu-Ka radiation has characteristic peaks at diffraction angles 2theta values ​​of 8.3±0.2°, 10.7±0.2°, 12.4±0.2°, 13.3±0.2°, 14.1±0.2°, 14.9±0.2°, 15.9±0.2°, 16.2±0.2°, 16.6±0.2°, 17.9±0.2°, 20.8±0.2°, 21.9±0.2°, 24.3±0.2°, 24.9±0.2°, 25.2±0.2°, 26.0±0.2°, 27.1±0.2°, 27.6±0.2°, 28.4±0.2°, 30.1±0.2°, and 31.9±0.2°.

2. A methotrexate hydrate crystalline form DCI according to claim 1, characterized in that: The differential scanning calorimetry spectrum of the crystalline form DCI shows endothermic peaks at 105±5°C and 181±5°C.

3. A methotrexate hydrate crystalline form DCI according to claim 1, characterized in that: The thermogravimetric analysis spectrum of the crystalline form DCI shows that the weight loss at 25-150°C is 10%-11%.

4. A methotrexate hydrate crystalline form DCI according to claim 1, characterized in that: The range of the hydrate is 2.5-3.

5. A method for preparing a methotrexate hydrate crystal form DCI, characterized in that: Disodium methotrexate is dissolved in water, and a sulfuric acid aqueous solution is added to precipitate a solid. The suspension is stirred, separated, and dried to obtain crystalline DCI.

6. The method for preparing a methotrexate hydrate crystal form DCI according to claim 5, characterized in that: The crystallization temperature is 0-50°C.

7. A pharmaceutical composition, characterized in that The pharmaceutical composition comprises an effective therapeutic amount of the methotrexate hydrate crystal form DCI according to claim 1 and a pharmaceutically acceptable carrier or excipient thereof.

8. Use of the methotrexate hydrate crystal form DCI according to claim 1 in preparing medicines.